Volt-ampere Characteristics of Metal-semiconductor Rectifier Diodes. Part 1: Formation of Conduction Currents and Displacement Currents at the p–n Junction - L. I. Gretchikhin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2025)
Electric currents arising in metal-semiconductor contact are represented as the sum of diffusion currents and drift currents. The use of various empirical formulas was proposed to determine their value. This approach to determining electric currents in metal-semiconductor diodes does not allow pinpointing experimentally obtained values of electric currents. In this regard, there was a problem in developing the theoretical foundations for the production of this type of equipment on a sufficiently sound theoretical basis, taking into account the latest achievements in electrical engineering and electronics. The theoretically calculated surface of triatomic molecules for silicon completely coincided with the experimental data obtained on a tunneling microscope. The process of applying a film made of germanium or silicon semiconductor to an aluminum metal base is considered. It is shown that the most optimal is the application of coatings by laser spraying. The concentration of free electrons in the conduction band of aluminum is determined, which occurs due to the ionization of negative ions and thermoautoelectronic emission of electrons from the metal under the influence of temperature and applied external voltage. A theory of the formation of electric currents of conduction and displacement has been developed. The conditions for the occurrence of an electric conduction current in columnar cavities on the aluminum surface and displacement currents in the supply wires are specified. It is shown how the conversion of conduction currents into a displacement current occurs at the boundary of the p–n junction.